2019
DOI: 10.1111/bre.12349
|View full text |Cite
|
Sign up to set email alerts
|

Impact of recycling and lateral sediment input on grain size fining trends—Implications for reconstructing tectonic and climate forcings in ancient sedimentary systems

Abstract: Grain size trends in basin stratigraphy are thought to preserve a rich record of the climatic and tectonic controls on landscape evolution. Stratigraphic models assume that over geological timescales, the downstream profile of sediment deposition is in dynamic equilibrium with the spatial distribution of tectonic subsidence in the basin, sea level and the flux and calibre of sediment supplied from mountain catchments. Here, we demonstrate that this approach in modelling stratigraphic responses to environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…Recycling has been identified as a major issue for interpreting the grain size and mineralogy of basins in terms of tectonics and climate, but it is difficult to prove and quantify 7 . Sediment recycling in an alluvial fan was recently shown to control the downstream gravel grain size variations in alluvial fans found in an arid Andean piedmont in Argentina 51 . Our data confirm that sediment storage and recycling occur even in this relatively short and confined river.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recycling has been identified as a major issue for interpreting the grain size and mineralogy of basins in terms of tectonics and climate, but it is difficult to prove and quantify 7 . Sediment recycling in an alluvial fan was recently shown to control the downstream gravel grain size variations in alluvial fans found in an arid Andean piedmont in Argentina 51 . Our data confirm that sediment storage and recycling occur even in this relatively short and confined river.…”
Section: Discussionmentioning
confidence: 99%
“…From these observations, a simplified self-similar solution for the long-term substrate grain-size distribution has been proposed 56 and successfully used to reconstruct subsidence rates and input flux histories in some examples 57,58 . A recent study has shown that this model is improved by including the lateral inputs of recycled sediments 51 . Our results confirm that lateral storage and recycling contributes to the downstream grain size evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of cosmogenic 21 Ne from pebbles of the modern North Platte River of Nebraska demonstrates that the majority of the coarse gravel of the river has experienced long periods (10 5 to >10 6 yrs) of floodplain storage and recycling, which explain the presence of pebbles hundreds of kilometers into the Great Plains (Sinclair et al 2019). Also, it has been demonstrated that there is a strong correlation between the degree of recycling of alluvial fans and the coarseness of three alluvial fans in the Iglesia Basin of Central Argentina (Harries et al 2019). However, most of these studies are based on the interpretation of old sedimentary series and, to date, there hasn't been a clear demonstration of the impact of recycling on the characteristics of the sediment (flux, shape, grain size distribution) exported by rivers, in particular with reference to modern river systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focus on five adjacent catchments, east of the Frontal Cordillera drainage divide, which feed three alluvial fans in the Iglesia basin (Harries et al, 2018(Harries et al, , 2019. The Palaeozoic basement exposed in these catchments is composed of two dominant lithological units of similar age (Figure 2a).…”
Section: Study Areamentioning
confidence: 99%
“…The development of these terraces lacks quantitative constraint, though elsewhere in the Andes, such cut and fill sequences have been linked to alternations between wet and dry periods on a variety of orbital timescales (Bekaddour et al, 2014;Litty et al, 2018;Norton et al, 2016;Siame et al, 1997;Steffen et al, 2009;Tofelde et al, 2017Tofelde et al, , 2019. We isolate three adjacent alluvial fans and focus on their modern rivers, which are currently incised~2 m into a surface interpreted to be Holocene in age (Harries et al, 2018(Harries et al, , 2019. The largest alluvial fan, fan 1, extends~40 km into the centre of the basin, and is fed by two large catchments (2 and 3 in Figure 2).…”
Section: Study Areamentioning
confidence: 99%